The Practice Of Digital Capitalism And The Commodification Of The Salafi Community On Instagram Rodjatv - Makroen SANJAYA; Andi Faisal BAKTI; Ridzki Rinanto SIGID; Rulli NASRULLAH (Indonesia Strategic Sustainability, 2022)
The Salafi community is known as a group of Islamic conservatism that seeks to preserve the rules of the Prophet Muhammad. Salafists, in general, seek to purify the teachings of Islam by rejecting modernity. However, Salafi media, Rodja, instead of utilized advances in modern communication technology to spread conservative ideology. Through Instagram, Salafi virtual communities practice digital capitalism. Therefore, the study aims to reveal how Salafi media Rodja utilizes features on Rodjatv's Instagram social media to attract followers and gain financial benefits through the practice of digital capitalism virtually. Using new media analysis in a qualitative approach to virtual ethnographic methods, the study explained how two characteristics of new media, namely interactivity and digital capitalism, could drive the participation of Salafi virtual communities. The results uncovered that religious content uploaded on Rodjatv's Instagram became a means of aggregation of Salafism followers, which were then employed to accumulate capital in media business activity. This practice of digital capitalism by Salafism later became an inspiration for other da'wah groups. On the other hand, communication and informatics authorities, together with legislative institutions, need to make clear regulations regarding the use of social media for the benefit of religious da'wah, because in addition to legal loopholes from the economic side, such as taxes and others, social media used by certain ideological groups tend to invite socio-political insecurity in the long term exclusively